2020
DOI: 10.1177/1591019920947878
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of flow diverter placement for intracranial aneurysm with dual antiplatelet therapy and oral anticoagulant therapy

Abstract: Purpose Antiplatelet therapy initiated before flow diverter placement is effective for the prevention of ischemic complications. However, the effectiveness of oral anticoagulant treatment is unclear. This retrospective study evaluated the complications and obliteration rates after flow diverter placement in patients taking anticoagulants. Methods A total of 155 cases were treated by Pipeline Flex placement for unruptured large and giant cerebral aneurysms in our hospital between October 2015 and June 2019. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, there is some evidence that more robust anticoagulation regimens can increase nonocclusion rates without additional clinical benefit. A limited retrospective study comparing patients on additional oral anticoagulants plus DAPT versus DAPT alone prior to flow diverter placement demonstrated that the complete obliteration rate of the excluded aneurysm was significantly lower in the oral anticoagulant group [11] , in keeping with our report.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is some evidence that more robust anticoagulation regimens can increase nonocclusion rates without additional clinical benefit. A limited retrospective study comparing patients on additional oral anticoagulants plus DAPT versus DAPT alone prior to flow diverter placement demonstrated that the complete obliteration rate of the excluded aneurysm was significantly lower in the oral anticoagulant group [11] , in keeping with our report.…”
Section: Discussionsupporting
confidence: 90%
“…We previously reported that anticoagulant medication causes reduced occlusion rate after FD implantation. 32) In particular, atrial fibrillation is a disease that increases with age, so we need to be cautious about anticoagulant therapy. In the present study, 2 patients from the group of patients who had undergone previous anticoagulation therapy were included in the current long-term follow-up group.…”
Section: Discussionmentioning
confidence: 99%
“…The other, for the first 6 months, was on dual antiplatelet therapy without oral anticoagulation before stopping the antiplatelets and resuming oral anticoagulation. Even worse radiographic outcomes were reported by Fujii et al 14…”
Section: Discussionmentioning
confidence: 81%
“…A single case series from the group at Juntendo University reported on eight patients undergoing flow diverting embolization of their cerebral aneurysms while on triple therapy of an oral anticoagulant and dual antiplatelet therapy. 14 While making no comment on systemic hemorrhagic complications, two of the eight treated patients suffered an intracranial hemorrhagic complication with delayed aneurysm rupture. In addition, six of the eight patients had continued filling of their aneurysms at last follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation